Gravity Gold 2010 : 21-22 September 2010, Ballarat, Victoria : [proceedings] - Dominy, Simon (AusIMM, 2010)
"Gravity Gold 2010 aims to explore the issues of mining operations that are characterised by coarse-gravity gold mineralisation with an often high-nugget effect."--Foreword
"Optimising recovery"--Cover
Keywords: Gold mines and mining -- Congresses.; Gold ores -- Congresses.; elektronické knihy; electronic books